Vibrational Spectroscopy in Diagnosis and Screening - Severcan, Feride (IOS Press, 2014)
Vibrational spectroscopy (infrared and Raman) has been at the forefront of scientific research, especially in the characterisation of molecular structure. This is evident from the following statement taken from a lecture by the Nobel laureate Linus Pauling (Sillman, Lecture, October, 1947) about the struggle to determine the structure of penicillin